Potential of Graphene–Polymer Composites for Ligament and Tendon Repair: A Review. Issue 12 (3rd September 2020) - Peixoto, Tânia; Paiva, Maria Conceição; Marques, António T.; Lopes, Maria A.
Abstract : Tendon/ligament injuries are debilitating conditions that affect the life quality of a great percentage of the adult population. Several challenges still have to be addressed regarding the repair of these tissues, as current treatments show limited success. The use of biocompatible and biodegradable polymeric scaffolds potentially helps accomplish a complete and long‐term functional repair but, unfortunately, these materials lack adequate mechanical properties to be used in such demanding applications. Graphene is a subject of interest for tissue‐repair applications due to its electrical conductivity and mechanical properties. If incorporated adequately, it may significantly improve the physical properties of the composite, even at small loadings. Furthermore, graphene presents a biocompatible surface that may enhance cell adhesion, proliferation and differentiation and demonstrates promising outcomes in several in vitro and in vivo biological applications. Therefore, herein, the potential of graphene materials for the reinforcement of biodegradable polymers of interest for tendon/ligament repair is explored. The effect of graphene on relevant features such as mechanical properties, biodegradability, and biocompatibility is revised, to understand the feasibility of these composites to fulfill the requirements associated with these tissues and conclude how their applicability is extended to this field. Abstract : As current strategies for tendon/ligament repair still show limited success, the search for a material that helps accomplish a long‐term functional repair continues. Graphene's unique combination of properties, including mechanical and biocompatibility, indicate its great potential for improving the performance of polymer composites. As such, herein, the potential of graphene‐based composites in this field is reviewed.